ANALYZING THE NEW TEACHERS’ SOCIALIZATION IN PAKISTAN: AN EMPIRICAL INTERPRETATION - Manzoor Ali; Abdul Rahim Chandio (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2022)
Teachers’ development and growth play a vital role as a bridge to enrich a civilized community the human capital and structure. The whole economic competition of the modern is directly linked with a good education which is based on teachers’ service to build the nation to meet the set goal of the communities. The present study encircles the attention on teachers’ development and growth using socialization in various aspects in a Pakistan context. Teachers’ socialization represents a complex process by which individuals selectively obtain the knowledge, values, norms, behaviour, skills, and attitude relating to the profession of teaching skills and acquire the particular educational culture within their work environment. The relationship between socialization and teachers’ development and growth-related factors was measured. The extant study pursues to interpret the relationship between teachers’ cooperation and collaborative practice, new teachers’ training (induction programs), Suitable placement of teachers in the school system, Government based Policy environment and Professional culture with the criterion variables of socialization and teachers’ development constructs were examined. Data collection has been carried out by the three regions of Sindh in which teachers’ participation was ensured. For data collection, survey items were distributed in which 219 respondents’ opinions were gathered and the empirical analysis was carried out by SPSS and also hypothetical validation was carried out. Moreover, a theoretical perspective was attached and recommendations and future direction were included in the prevailing study.